Javanese patriarchal culture of gender stereotypes in the English translation of Gadis Kretek: a critical discourse analysis - Nunun Tri Widarwati; Budi Purnomo (Cogent Arts & Humanities, 2025)
The persistence of Javanese patriarchal culture and gender stereotypes is a pressing concern in contemporary Javanese society. Consequently, in recent years, a growing number of literary works have been translated into English to portray the patriarchal culture globally. This study aims to conduct a critical discourse analysis of the English Translation of a novel entitled Gadis Kretek to examine how the translation of the novel portrays gender roles and stereotypes within the Javanese patriarchal culture. The findings of this study revealed that five out of the ten components of sexist discourse appear in the translation of the novel ‘Cigarette Girl’ by Ratih Kumala including negative evaluation of women, males as the norms, women are weak, women are no more than possession, and valuing women based on their appearance. These elements highlight various forms of sexism in discourse, particularly in the portrayal of women. This research implication highlights the critical role translators play not just as linguistic bridges, but as active cultural mediators whose choices can either challenge or hold entrenched gender biases on a global scale.